Implementation of double-layer loaded on octagon microstrip yagi antenna - Kamelia Quzwain; Alyani Ismail; Yudiansyah Yudiansyah; Nadia Media Rizka; Aisyah Novfitri; Lia Hafiza (Institute of Advanced Engineering and Science, 2021)
A double-layer loaded on the octagon microstrip yagi antenna (OMYA) at 5.8 GHz industrial, scientific and medical (ISM) Band is investigated in this paper. The double-layer consist of two double positive (DPS) substrates. The OMYA is overlaid with a double-layer configuration were simulated, fabricated and measured. A good agreement was observed between the computed and measured results of the gain for this antenna. According to comparison results, it shows that 2.5 dB improvement of the OMYA gain can be obtained by applying the double-layer on the top of the OMYA. Meanwhile, the bandwidth of the measured OMYA with the double-layer is 14.6%. It indicates that the double-layer can be used to increase the OMYA performance in term of gain and bandwidth.